Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0138041
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Human Turbinate-Derived Mesenchymal Stem Cells Are Not Affected by Allergic Condition of Donor

Abstract: The characteristics of mesenchymal stem cells (MSCs) derived from human turbinates (hTMSCs) have not been investigated in allergic rhinitis. We evaluated the influence of allergic state of the donor on the characteristics, proliferation, and differentiation potential of hTMSCs, compared with hTMSCs derived from non-allergic patients. hTMSCs were isolated from five non-allergic and five allergic patients. The expression of toll-like receptors (TLRs) in hTMSCs was measured by FACS, and cell proliferation was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The immune imbalance between Th1 and Th2 cells is the immunological basis of the incidence of AR, that is, the incidence of AR is mainly the advantage of Th2 cell immune response, 30 which leads to a series of nasal allergy symptoms by mediating the release of a variety of inflammatory mediators and cytokines. 31 Th2 cells initiate and maintain inflammation in allergic immune response by releasing large amounts of Th2 cytokines (interleukin (IL)-4, IL-5, IL-13, etc).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immune imbalance between Th1 and Th2 cells is the immunological basis of the incidence of AR, that is, the incidence of AR is mainly the advantage of Th2 cell immune response, 30 which leads to a series of nasal allergy symptoms by mediating the release of a variety of inflammatory mediators and cytokines. 31 Th2 cells initiate and maintain inflammation in allergic immune response by releasing large amounts of Th2 cytokines (interleukin (IL)-4, IL-5, IL-13, etc).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, regulating Th1/Th2 immune balance may play an important role in the treatment of allergic inflammation, which is also an important entry point in treatment. 30 Genç et al 33 co-cultured pulp-derived MSC (DFSC) with Peripheral blood mononuclear cell (PBMC) of patients with asthma, measured the proliferation of CD4+ T lymphocytes by carboxyfluorescein diacetate succinimidyl ester (CFSE) staining combined with flow cytometry, and found that DFSC could inhibit the proliferation of CD4+ T lymphocytes. The relative expression levels of IL-4 and GATA-3 mRNA were decreased, the relative expression levels of interferon-γ, T-bet and IL-10 were increased, and the percentage of Tregs was increased.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was proved that the hTMSCs exhibited approximately 5 times higher proliferation than the hBMSCs [ 15 ]. 3 Additionally, it has been shown that the donor age do not influence the properties of hTMSCs, unlike other human MSCs [ 4 ] and local condition of nasal cavity including allergic state or nasal septal deviation also do not have the effect on the feature of them [ 16 , 17 ]. The excellent potency of hTMSCs compared to MSCs from other tissues could make our group pay particular attention to the cells.…”
Section: Discussionmentioning
confidence: 99%
“…The glass cover slide was removed, and cells attached to the culture plate were harvested using 0.25% trypsin in 1 mM EDTA solution. Similar to types of MSCs, hTMSCs have a high proliferative capacity and the ability to differentiate into multiple lineage cell types. ,,, hTMSCs were expanded in three to four passages for use in experiments. hBMSCs were obtained from the Catholic Institute of Cell Therapy (Catholic MASTER Cells, Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%